Alleviating Overgrazing Stress and Promoting Grassland Plant Regeneration via Root Exudate-Mediated Recruitment of Beneficial Bacteria - Ting Yuan; Jiatao Zhang; Shaohong Zhang; Shuang Liang; Changhong Zhu; Weibo Ren; Jialu Liang (Microorganisms)
Overgrazing (OG) is an important driver of grassland ecosystem degradation and productivity decline. Plants may effectively cope with OG stress by regulating their synergistic interactions with plant growth-promoting rhizobacteria (PGPR) through root exudates. However, the synergistic regulatory mechanisms remain unclear. Under OG stress, Leymus chinensis recruited the specific PGPR strain Paraburkholderia graminis (B24) by regulating specific root exudate compounds, including amino acids, alkaloids, and organic acids, which enhance B24 chemotaxis and biofilm formation. The B24 inoculation systematically regulated the transcription of key plant growth and development genes, including those involved in nutrient transport and cell wall expansion, which enhanced nutrient uptake and promoted the overall growth of L. chinensis. Furthermore, B24 regulated the homeostasis of endogenous L. chinensis through the synergistic effects of hormones and the trade-off between growth and defense. Integrated transcriptomic and metabolomic analyses revealed that B24 regulation enhanced carbon and nitrogen metabolism, and energy supply after mowing, forming a holistic adaptive mechanism that enabled L. chinensis to effectively recover from mowing-induced stress, thereby improving its adaptability and regenerative capacity. This study provides a scientific basis and support for elucidating the response mechanisms of how grassland plants cope with OG stress, optimizing grassland management, and rapidly restoring and enhancing grassland productivity.